MANAGEMENT STRATEGY OF ELEPHANT RIDING AT THE ZOO - Sata Yoshida Srie Rahayu; Dolly Priatna; Rosadi Rosadi; Suryanto Suryanto (Indonesian Journal of Forestry Research, 2022)
Elephant Riding (ER) in zoos has become a matter of public interest, raising debates among experts regarding animal ethics, elephants’ welfare, and human safety. Through the submission of the Middle Hypothesis that ER tends to enhance human knowledge about conservation, this study’s aim is to provide strategies to help zoo managements in their works  based on the basic principles of wildlife conservation and protection, especially Sumatran elephants. The participants’ knowledge was measured using questionnaires distributed to two groups of respondents: people who have and people who have not utilized ER services. Meanwhile, the strategy was recommended through the Analytical Hierarchy Process of 17 expert respondents. According to the independent sample t-test performed with  95% confidence level, human knowledge of elephant conservation increased significantly through ER. Furthermore, experts with consistency ratios (CR) ≤ 0.1 selected a strategy where environmental quality was prioritized as a recommended strategy in ER management. This strategy is to put forward the principles guaranteeing the elephants’ welfare, which has a criterion weight of 0.40717. The other recommended strategies include conducting conservation education (0.23973), ensuring the safety of visitors (0.22972), and improving the welfare of the community around zoo (0.12338).